Design of Wedding Organizer Information System at "Bella W-O" using the waterfall method - SAYUTI, AKHMAD; Serry Davizan; Irwansyah (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
Wedding Organizer services help prospective brides and grooms and families plan their weddings. This service is popular because it makes wedding planning easier. However, the obstacle or problem is that wedding service promotions often face challenges such as incomplete wedding package information and manual transaction data processing that can cause errors. This study reveals that the Wedding Organizer application can provide complete information about wedding packages, update the latest package list, handle transactions in real-time, and manage order information automatically. This study uses the waterfall method which includes the stages of analysis, implementation, testing, and maintenance. Data collection methods include wedding package data, photo gallery data, and vendor data. System development follows a prototype model with stages of communication, rapid planning and modeling. The programming language used is the PHP programming language, with MySQL as the Database Management System (DBMS).